LncRNAs and Rheumatoid Arthritis: From Identifying Mechanisms to Clinical Investigation - Huang, Wentao; Li, Xue; Huang, Chen; Tang, Yukuan; Zhou, Quan; Chen, Wenli (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is a systemic chronic autoinflammatory disease, and the synovial hyperplasia, pannus formation, articular cartilage damage and bone matrix destruction caused by immune system abnormalities are the main features of RA. The use of Disease Modifying Anti-Rheumatic Drugs (DMARDs) has achieved great advances in the therapy of RA. Yet there are still patients facing the problem of poor response to drug therapy or drug intolerance. Current therapy methods can only moderate RA progress, but cannot stop or reverse the damage it has caused. Recent studies have reported that there are a variety of long non-coding RNAs (LncRNAs) that have been implicated in mediating many aspects of RA. Understanding the mechanism of LncRNAs in RA is therefore critical for the development of new therapy strategies and prevention strategies. In this review, we systematically elucidate the biological roles and mechanisms of action of LncRNAs and their mechanisms of action in RA. Additionally, we also highlight the potential value of LncRNAs in the clinical diagnosis and therapy of RA.